2018
DOI: 10.5006/2860
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Electro-Chemical-Soil Model to Evaluate the Influence of Soil Aeration on Underground Metal Pipe Corrosion

Abstract: A mechanistic understanding of the process of underground corrosion is important for modeling pipeline deterioration. In this study, a time-dependent multiscale numerical model incorporating electrochemistry and soil hydrology is developed. The model realistically simulates soil moisture and aeration conditions and their influence on anodic/cathodic activity without prior definition. In this manner, both micro- and macrocell corrosion and their evolution with time are simulated along with the effects of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…However, this study does not consider factors that accentuate such effects such as passivation and corrosion product deposition. These effects and their time-dependent influence on corrosion were discussed in a previous paper [12]. The 3D simulation involving a hypothetical saturation distribution shows that the level of corrosion becomes a maximum corresponding to the optimum point, while also highlighting the development of macro cells due to differential aeration.…”
Section: Practical Implicationsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, this study does not consider factors that accentuate such effects such as passivation and corrosion product deposition. These effects and their time-dependent influence on corrosion were discussed in a previous paper [12]. The 3D simulation involving a hypothetical saturation distribution shows that the level of corrosion becomes a maximum corresponding to the optimum point, while also highlighting the development of macro cells due to differential aeration.…”
Section: Practical Implicationsmentioning
confidence: 81%
“…To ascertain the active area, the corroded electrode surfaces were digitally imaged after each polarisation test. Subsequently, the images were thresholded using Otsu's algorithm [19] and the active area, normalised to the total electrode area, were determined [12]. The relationship between the active area and the degree of saturation was established in this manner.…”
Section: Active Area Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Equations 4-8 one can estimate oxygen accessibility at the electrode surface within the soil [14].…”
Section: The Effect Of Temperature and Ionic Solutes On Dissolved O₂ ...mentioning
confidence: 99%
“…Using a numerical model, it was shown that differential aeration can lead to severe corrosion of a buried pipeline [14].…”
Section: Introductionmentioning
confidence: 99%